The Role of the Judiciary Within the Construction of Collective Memory. The Italian Transition - Caroli, Paolo (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
At the end of World War II, Germany and Japan were undoubtedly the defeated powers of the Axis and they were put on trial in Nuremberg and Tokyo respectively. Italy, by contrast, had vague and multiple identities and underwent a complex and heterogeneous transitional process. The criminal prosecution of war crimes was based on a double path, which varied depending on the nationality of the perpetrators: Italian or German. This starting point paved the way for future memory paths: the increased hiding of Fascist crimes in the shadow of the ones committed by the Nazis. This article describes how Italy has been dealing with Fascist and Nazi crimes and with its own national responsibilities. It focuses in particular on the activism of the judiciary, between the 40s and the 50s, in favour of Fascist criminals, especially in the application of the so called Togliatti Amnesty. The article also aims to show how the judicial prosecution influenced the collective memory of those crimes within Italian society.
Keywords: ściganie zbrodni wojennych; zbrodnie faszystowskie; sądownictwo; pamięć zbiorowa; społeczeństwo włoskie